An appraisal of uranium source potential of granites, associated felsic rocks, kaolin and calcretes of Nagar Parkar area, Tharparkar Pakistan - Ali, Munazzam; Shariff, Aqeel Ahmed; Qamar, Naser Ali; Laghari, Amanullah (Journal of Himalayan Earth Sciences, 2013)
In this study geochemistry of Nagar Parkar intrusives has been discussed in detail with particular reference to uranium. The uranium content of southern and eastern plutons is relatively higher as compared to the northern part of the complex. It has been a general tendency that the uranium concentration in pink granites is more pronounced. Negative disequilibrium was observed in some samples of granites and kaolins, indicating labile uranium from the system. Major element data revealed that the alkali and alumina contents are in accordance with the uranium productive granites, while silica concentration is higher than the favorable range. So the chances to host any primary mineralization within the granites are not very high. Trace elements pattern and low aegirine-riebeckite concentrations propose that the pink granites have strong crustal input, and may be more favorable for uranium concerns. The uranium data of kaolins indicates the availability of active (leachable) uranium in the system, and subsequent redistribution by circulating ground water might have created a zone of concentration within the kaolins. Additionally, calcretes and lignite related Paleocene sandstones in the Thar coal basin, immediately north of the granitic terrain are the prospective hosts for the labile uranium. Rate of disintegration of the rocks, size and relative age also suggest that the pink granites are more likely the source for any secondary mineralization in a nearby host. The granites may be considered as moderate source for any subsequent small scale uranium deposit.